Design and Build a Monitoring and Analysis System for Toddler Posyandu Activities at Web-Based Baperkam Sunyaragi - Linda Norhan; Tedi Kustandi (Politeknik Siber Cerdika Internasional, 2026)
Background: A web-based monitoring and analysis system for toddler weighing data at the Sunyaragi Community Health Agency (Baperkam) was designed to simplify the recording and management of toddler weighing data. Currently, the process of recording toddler weighing data at Baperkam Sunyaragi is still done manually, making it prone to recording errors, delays in data processing, and difficulties in analyzing toddler growth. Objective: This research aims to develop a web-based application that can monitor and analyze toddler weighing data more efficiently and accurately. Methods: The method used in this research is software development using the waterfall approach, which includes the stages of needs analysis, system design, implementation, testing, and evaluation. The developed application facilitates information access for health workers and parents of toddlers. Results: The results show that the developed system can improve data recording efficiency, accelerate the analysis process, and reduce input errors. Conclusion: However, this research has limitations in its scope of use: it is still limited to a single location and requires training for new users. This research is expected to contribute to the use of information technology in the health sector, particularly in monitoring the nutritional status of toddlers, and serve as a basis for further development for implementation in various other health service locations.